2013
DOI: 10.1073/pnas.1319502110
|View full text |Cite|
|
Sign up to set email alerts
|

Antitumor activities of agonistic anti-TNFR antibodies require differential FcγRIIB coengagement in vivo

Abstract: Significance Agonistic antibodies targeting key TNF receptor (TNFR) molecules involved in antitumor responses have been demonstrated as potent antitumor therapies in preclinical studies. However, no effective agonistic anti-TNFR therapies have been successfully developed to date. In contrast, cytotoxic antitumor antibodies targeting tumor antigens or antagonistic antibodies blocking key inhibitory checkpoints are widely used in clinical settings. One explanation for this discrepancy has been recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
84
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 28 publications
5
84
0
Order By: Relevance
“…Our findings add to the growing body of evidence showing the importance of Fc-FcgRIIb interactions for the activity of agonistic mAbs targeting tumor necrosis factor receptor (TNFR) superfamily members such as CD40, TNF-related apoptosis-inducing ligand (TRAIL), and death receptor 5 (DR5), where Fc-FcgRIIb interactions are crucial for activity. [20][21][22][23] In these experiments, we did not observe any change in the sensitivity of the T cells themselves to TGN1412 after HD preculture in contrast to previous studies, which suggested that HD preculture resulted in enhanced tonic TCR signaling causing a reduction in the activation threshold of the T cells in vitro. 9,24,25 Ongoing studies show that other immunostimulatory mAbs, including anti-OX40 and anti-4-1BB, show similar HD preculture dependency for increased activatory activity (data not shown), suggesting that this assay will have considerable utility for predicting the potency and perhaps toxicity for many FcgRIIb-dependent agonistic mAbs.…”
Section: Discussionsupporting
(Expert classified)
See 1 more Smart Citation
“…Our findings add to the growing body of evidence showing the importance of Fc-FcgRIIb interactions for the activity of agonistic mAbs targeting tumor necrosis factor receptor (TNFR) superfamily members such as CD40, TNF-related apoptosis-inducing ligand (TRAIL), and death receptor 5 (DR5), where Fc-FcgRIIb interactions are crucial for activity. [20][21][22][23] In these experiments, we did not observe any change in the sensitivity of the T cells themselves to TGN1412 after HD preculture in contrast to previous studies, which suggested that HD preculture resulted in enhanced tonic TCR signaling causing a reduction in the activation threshold of the T cells in vitro. 9,24,25 Ongoing studies show that other immunostimulatory mAbs, including anti-OX40 and anti-4-1BB, show similar HD preculture dependency for increased activatory activity (data not shown), suggesting that this assay will have considerable utility for predicting the potency and perhaps toxicity for many FcgRIIb-dependent agonistic mAbs.…”
Section: Discussionsupporting
(Expert classified)
“…21 Work with CD40 has shown that simply cross-linking the receptors is sufficient for activity and that no downstream signaling is required. 20,23,30 Whether the same holds true for TGN1412 and CD28 remains to be confirmed.…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly, in the present study we show in vivo induction of PCD mediated via cross-linking by the activating FcgRs for a target that does not belong to the TNFR superfamily. Because NOTAM mice carry a signaling-inactive FcRg-chain, the FcgR-mediated cross-linking of DARA resulting in PCD is FcgR signaling-independent, as was similarly observed for agonistic TNFR-targeting Abs (42). The long-term effect of DARA in this syngeneic i.p.…”
Section: Discussionmentioning
confidence: 54%
“…As FDC are also a source of captured Ag, they may represent an ideal cell type for augmenting further Ag presentation and processing for subsequent T cell stimulation. This observation may therefore relate to the potent immune stimulating activity of mAb targeting TNF receptor super family members such as CD40 and DR4/5 (12)(13)(14)50). In contrast to direct targeting mAb such as rituximab, which are impaired by mFcgRII and hFcgRIIB, these receptors are now known to be an important component of immunomodulatory mAb activity, where they serve to further cross-link the target receptor for optimal signaling (20)(21)(22)(23)(24)(25)reviewed in Ref.…”
Section: Discussionmentioning
confidence: 99%